Bukovynian Hytsuls’ Religious Picture of the World Through Addresses to Higher Forces in the Works by Yuriy Fedkovych (Linguostylistic Studies, 2015)
The article deals with the analysis of addresses in the works by Yuriy Fedkovych as an important means of verbalization of religious worldview in the nineteenth century. The authors point out that the distinctive feature of Bukovynian writer’s individual style is frequent appeal to higher forces. Despite the widespread belief that pagan views prevail in the Hutsuls’ worldview, Yuriy Fedkovich positioning himself as their representative, language means of verbalization of the addressed speech in the works under analysis show that paganism is reflected only in stylized folklore works or works on historical themes, and in general Christian ideas dominate. In addition to an important function of disclosure of Bukovynians’ language picture of the world, names-addresses to the religious concepts have important stylistic functions: they make texts more emotional, sincere, provide colloquial or elated coloring. Key words: religious picture of the world, language picture of the world, addressed speech, address, pagan ideas, Christian ideas. References